EFEKTIVITAS MANAJEMEN SARANA PRASARANA DI BALAI PELATIHAN OPERASI DAN PEMASARAN AGUS SUROTO PT KERETA API INDONESIA (PERSERO) BANDUNG) (Jurnal Tata Kelola Pendidikan, 2020)
The theme of this research is "The Effectiveness of Management Facilities at the TrainingCenter Operations and Marketing Agus Suroto PT Kereta Api Indonesia (Persero)Bandung”. management facilities is the process of procuring and utilizing componentsboth directly and indirectly in the education process to achieve effective and efficienteducational goals. Effectiveness is reviewed by the approach of objectives, systems,constituency strategies, competitive value. The objectives of this study are 1) Obtain anoverview of the effectiveness of Facilities Management in the Training Center Operationsand Marketing Agus Suroto PT Kereta Api Indonesia (Persero) Bandung. 2) obtain anoverview of the obstacles in the management of facilities and infrastructure at BP OPSARPT KAI (Persero). 3) Measuring the efforts made in overcoming the strongest obstacle ofmanaging facilities and infrastructure in the Training Center Operations and MarketingAgus Suroto PT Kereta Api Indonesia (Persero) Bandung. This study uses qualitativeresearch because it investigates direct phenomena and describes in depth. The findings inthis study are described in accordance with the research questions, namely: 1) Having aneffective approach in its implementation, the organizing committee has succeeded incommunicating with teachers and students in realizing effective infrastructure managementgoals that refer to the vision and mission of the training center. The systems approachconsists of an input-process-output, monitoring and evaluation system. The strategicconstituency approach is evidenced by the organizing committee and instructors who areable to meet the needs of infrastructure for the needs of stakeholders during trainingactivities, and the training center measurement reference is to obtain accreditationcertification given by the director general. The training center's competitive valueapproach applies modernization innovations. 2) Inhibiting factors, namely technicalerrors, teacher negligence in filling in the TTD and the date on the student satisfactionevaluation form, student problems, there has been no improvement in the modernization oftools in the mechanical laboratory the problem is due to illness, the committee assessesgraduation with a score indicator.
Keywords: Management; Facilities; Effectiveness